An analysis of the legal framework for governing acid violence in Malaysia; with special references to the legal position in India and Bangladesh / Noradibah Khalidin, Salma Sakeena Mohamad Hassan and Siti Norshila Jamil - Khalidin, Noradibah; Mohamad Hassan, Salma Sakeena; Jamil, Siti Norshila (2012)
This research has been conducted to analyze the existing legal framework in Malaysia governing acid violence, where, special references have been made to the legal position in India and Bangladesh. The research aims to examine the adequacy of Malaysian law regarding the sale of certain types of acid commonly used in the attack, and also the means or mechanisms of remedy or compensation that can be provided to the victims, as well as to scrutinize any protection measures available to the victims. This is because acid violence victims are inflicted with severe physical, psychological and social scarring. Despite the gravity of the situation, there is still limited access to medical or psychological assistance to them, and the current law has been submitted to be inadequate in providing awareness to the public. Although the issue of acid violence is seasonal in Malaysia, the research attempts to take precautionary steps towards this issue, and for that matter, the legal position in India and Bangladesh have been chosen as references because of their experiences in handling the acid violence, as the issue had been long subsisted in their countries. Admittedly, Malaysia's acid attack rating may seem insignificant compared to other countries, but we seek for our country to take the lead in perfecting the people's need, be it from the smallest issue to the biggest. Therefore, at the end of the research, several recommendations have been laid out in hope that they could fill the gaps in the knowledge on the current laws governing acid violence in Malaysia.